Penguatan Kompetensi Digital-Pedagogis Guru Sekolah Dasar Melalui Pelatihan Educaplay Berbasis Game-Based Learning: Pengabdian - Muhammad Misbahudholam AR; Yeni Puji Astuti; Sama’; Choli Astutik (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Digital transformation requires elementary school teachers not only to operate technology but also to integrate it pedagogically, safely, and in accordance with student characteristics. This community service activity aims to strengthen teachers' digital competence through the development of game-based learning media using Educaplay. The activity was conducted at SDN Kebunagung II, Sumenep Regency, with the participation of 18 teachers. The method applied was participatory training based on partner needs, which included the stages of needs assessment, community education, enforcement, hands-on practice, mentoring, evaluation, and reflection. Data were collected through process and skills assessment sheets, product assessment rubrics, post-training questionnaires, reflective discussions, and activity documentation, then analyzed descriptively. The results showed that understanding of game-based learning concepts reached 83.3% in the very good category. Introduction to Educaplay features reached 78.9%, the ability to operate the platform 76.7%, and the ability to produce creative media 74.4%; these three indicators were in the good category. A total of 14 teachers or 77.8% understood the material well and stated they were ready to implement Educaplay in the classroom. However, only 11 teachers or 61.1% were able to produce media independently or with minimal assistance. The results of the activity indicate initial strengthening in understanding, operational skills, and readiness for implementation; However, continued mentoring is necessary to ensure more equitable and sustainable development of pedagogical design abilities.